Medial Meniscus Posterior Root Tear Treatment: A matched cohort comparison of non-operative management, partial meniscectomy and repair. Issue 7 (31st July 2020) - Bernard, Christopher; Tagliero, Adam; LaPrade, Matthew; Camp, Christopher; Saris, Daniel; Levy, Bruce; Stuart, Michael; Krych, Nicholas Kennedy Aaron
Objectives: Meniscal root disruption results in a loss of hoop strain resistance, increased articular cartilage contact pressure, and acceleration of degenerative changes. There is limited data comparing the outcomes of similarly matched patients with a medial meniscus posterior root tear treated with non-operative management, partial meniscectomy, or repair. The purpose of this study is to compare treatment failure, clinical outcome scores, and radiographic findings for a matched cohort of patients who underwent either non-operative management, partial meniscectomy, or transtibial pull-through repair for a medial meniscus posterior root tear (MMPRT). Our hypothesis is that patients who underwent meniscus root repair will have lower rates of progression to arthroplasty than patients who were treated with non-operative management or partial meniscectomy. Methods: Patients who underwent transtibial medial meniscus posterior horn root repair were matched by meniscus laterality, age, sex and K-L grades to patients treated non-operatively or with a partial meniscectomy. Progression to arthroplasty rates, IKDC and Tegner scores, and radiographic outcomes were analyzed between groups. Results: Forty-five patients were included in this study (15 non-operative, 15 partial meniscectomy, 15 root repair). Progression to arthroplasty demonstrated significant differences among treatment groups at a mean 74 months (non-operative 4/15, partial meniscectomy 9/15, meniscus repair 0/15, p=.0003). The meniscus root repair group had significantly less arthritic progression, as measured by change in K-L grade from pre-op to post-op (non-operative 1.0, partial mensicectomy 1.1, and meniscus repair 0.1, p=.001). Conclusion: Meniscus root repair leads to significantly less arthritis progression and subsequent knee arthroplasty compared to non-operative management and partial meniscectomy in a demographically matched cohort.